Profile and Prospect of Development of Buffalo in Bombana District, Southeast Sulawesi - Sani, La Ode Arsad; Rianse, Usman; Badaruddin, Rusli; Aku, Achmad Selamet (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Profile and Prospect of Development of Buffalo in Bombana District,Southeast Sulawesi